2018
DOI: 10.1177/1351010x18776431
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different in situ measurements techniques of intelligibility in an open-plan office

Abstract: Acoustic comfort in open-plan offices is a relatively recent research topic and some practices have not yet been consolidated. The goal in these spaces is to achieve good speech privacy at every workstation, reaching a high value of spatial decay of the sound pressure level. In case of refurbishment, a proper measurement of intelligibility criteria is needed, for example, in order to properly calibrate a numerical model or to plan acoustic treatments. This work compares different measurement techniques to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…This guarantees that different operators obtain similar measurement results from the same office as shown by the Round Robin test of Hongisto et al [7]. D'Orazio et al [8] reported measurement results from the office where the background noise level, L p,A,B , varied even 13 dB within a single measurement path. ISO 3382-3 [6] states that the mean of L pA,B values along the measurement positions shall be used in the position-dependent STI determinations.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…This guarantees that different operators obtain similar measurement results from the same office as shown by the Round Robin test of Hongisto et al [7]. D'Orazio et al [8] reported measurement results from the office where the background noise level, L p,A,B , varied even 13 dB within a single measurement path. ISO 3382-3 [6] states that the mean of L pA,B values along the measurement positions shall be used in the position-dependent STI determinations.…”
Section: Introductionmentioning
confidence: 62%
“…The limit values for classes A to D became 5, 7, 9, and 11 m for rC. The ranges for classes A-D are [0-5) m, [5][6][7] m, [7][8][9] m, and [9][10][11] Using the same criteria, the proposed limit values for classes A to D became 11, 9, 7, and 5 dB for D 2,s , 47, 49, 51, and 53 dB for L p,A,S,4m , and 6, 8, 10, and 12 m for r D .…”
Section: Resultsmentioning
confidence: 99%
“…The significant role played by speech intelligibility is on the basis of several analysis, measurements, and studies carried out in Spanish, Portoguese, Italian, English, and American churches. 6 The Speech Transmission Index ( STI ), defined by IEC 60268-16:2011, 9 describes the quality of the speech communication that closely depends on the signal-to-noise ratio (SNR), 10 where the signal is the sound pressure level at the receiver position.…”
Section: Acoustic Comfort In Churchesmentioning
confidence: 99%
“…In article [8], the DIRAC software application was used to compare the results of STI measurements by direct and indirect methods. Exponential sweep signal was used in indirect STI measurements.…”
Section: Introductionmentioning
confidence: 99%